2016
DOI: 10.1177/0301006616680124
|View full text |Cite
|
Sign up to set email alerts
|

Facial Redness Increases Men’s Perceived Healthiness and Attractiveness

Abstract: Past research has shown that peripheral and facial redness influences perceptions of attractiveness for men viewing women. The current research investigated whether a parallel effect is present when women rate men with varying facial redness. In four experiments, women judged the attractiveness of men's faces, which were presented with varying degrees of redness.We also examined perceived healthiness and other candidate variables as mediators of the redattractiveness effect. The results show that facial rednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 53 publications
(72 reference statements)
1
39
1
Order By: Relevance
“…The sexual dimorphism results indicated that while masculinity is clearly not preferred in female faces (d = 1.00), neither is increased femininity (d = .34). As the forced choice paradigm can only establish relative preferences, research teasing apart the direction of manipulation effects have often found that participants exhibit a relative preference for the unmanipulated stimuli to the 'decreased' version, rather than a preference for the 'increased' version [68,69,76]. That is, rather than preferring increased femininity in faces, participants dislike masculinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sexual dimorphism results indicated that while masculinity is clearly not preferred in female faces (d = 1.00), neither is increased femininity (d = .34). As the forced choice paradigm can only establish relative preferences, research teasing apart the direction of manipulation effects have often found that participants exhibit a relative preference for the unmanipulated stimuli to the 'decreased' version, rather than a preference for the 'increased' version [68,69,76]. That is, rather than preferring increased femininity in faces, participants dislike masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore unclear whether observers actually find more feminine faces more attractive, or find masculinised faces less attractive. Research in other areas of face perception has found that when examining a trait of interest using forced choice methodology, comparing manipulations to unaltered faces results in observers avoiding the low levels of a trait, rather than demonstrating a preference for high levels of a trait [68,69], which is the way the findings are typically interpreted. This pattern is consistent with the overgeneralisation hypothesis [30] -attractiveness perceptions are geared towards avoiding poor choices of mate, rather than seeking out the highest quality partners.…”
Section: Two-alternative Forced Choice Paradigmsmentioning
confidence: 99%
“…For example, when one sees a man in a red shirt, the color red can be associated with blood from a fight, implying aggression and facilitating competition . Alternatively, the color red can also be associated with blood oxygenation under the skin, implying health and facilitating perceived attractiveness . According to our hypothesis, red in this example is first associated with blood (object, concrete meaning), which then implies different concepts (abstract meaning) under different contexts (boundary condition) to exert disparate psychological effects.…”
Section: Discussionmentioning
confidence: 83%
“…32 Alternatively, the color red can also be associated with blood oxygenation under the skin, implying health and facilitating perceived attractiveness. 33 According to our hypothesis, red in this example is first associated with blood (object, concrete meaning), which then implies different concepts (abstract meaning) under different contexts (boundary condition) to exert disparate psychological effects. This hypothesis provides a complementary way to understand color effects and requires additional evidence from further research.…”
Section: Figurementioning
confidence: 91%
“…It is also possible that hormonal contraceptives have on-205 going and long-term effect on red skin colour (e.g., female odours [39,40]), a question that I 206 could not address in the present study and requires further investigation. Alternatively, colour 207 changes in the facial skin may be more condition-dependent and related to individual health, 208 thus masking a potential cycle effect [15,16,41]. Humans may have inherited the biological bases for female red skin colour and sexual 226 signalling from a primate ancestor.…”
Section: Determination Of the Estimated Ovulation 116mentioning
confidence: 99%